2012
DOI: 10.1142/s0217979213450306
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Discord in the Ground State of Spin Chains

Abstract: The ground state of a quantum spin chain is a natural playground for investigating correlations. Nevertheless, not all correlations are genuinely of quantum nature. Here we review the recent progress to quantify the 'quantumness' of the correlations throughout the phase diagram of quantum spin systems. Focusing to one spatial dimension, we discuss the behavior of quantum discord close to quantum phase transitions. In contrast to the two-spin entanglement, pairwise discord is effectively long-ranged in critical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 94 publications
1
44
0
Order By: Relevance
“…A systematic analysis in this sense, which has only recently been considered [7][8][9][10][11][12][13], is thus highly desirable. This is even more important given that some of the investigations performed so far have indicated that quantum discord is more sensible than entanglement in revealing quantum critical points [9], even for systems that are not at zero temperature [14]. This is a particularly relevant result, whose validity should also be checked for models that are both finite sized and at finite temperature.…”
mentioning
confidence: 95%
“…A systematic analysis in this sense, which has only recently been considered [7][8][9][10][11][12][13], is thus highly desirable. This is even more important given that some of the investigations performed so far have indicated that quantum discord is more sensible than entanglement in revealing quantum critical points [9], even for systems that are not at zero temperature [14]. This is a particularly relevant result, whose validity should also be checked for models that are both finite sized and at finite temperature.…”
mentioning
confidence: 95%
“…Discord has also been studied in the ground state of certain spin chains particularly close to quantum phase transitions [55]. Signatures of chaos in the dynamics of quantum discord are found using the model of the quantum kicked top [56].…”
Section: Quantum Discordmentioning
confidence: 99%
“…These states represent, for example, the general form of reduced density operators of arbitrary quantum spin chains with Z 2 (parity) symmetry (for a review see, e.g., Ref. [20]). The trace-norm correlation measures have been analytically developed for a general X state [37,38], reading…”
Section: Applicationsmentioning
confidence: 99%